Use of medicinal plants by black women: ethnography study in a low-income community - Rosa, Patricia Lima Ferreira Santa; Hoga, Luiza Akiko Komura; Santana, Mônica Feitosa; Silva, Pâmela Adalgisa Lopes (Revista da Escola de Enfermagem da USP, 2014)
Objective To explore beliefs, values and practices related to the use of medicinal plants among low-income black families. Method The research method was ethnography and the participant observation process was done in a low-income community in the peripheral area of the City of São Paulo. Twenty black women were interviewed. Results Two cultural sub-themes, I do use medicines that I learned to make with my mother and with religious practitioners to care for diseases and Home medicines are to treat problems that are not serious, and the cultural theme I do use home medicines to treat simple diseases because I always have them at my disposal, they are free and I don’t need a medical prescription represent beliefs, values, and practices related to the use of medicinal plants among low-income black families. Conclusion The development of such practices, which can hide ethnic and social vulnerability, reveals the resilience of low-income black women in the process of confronting problems during the health-illness process.